Le point de vue d’un assureur - Ross, Jacques (Assurances)

(untitled) (HEC Montréal, 1988)
Our readers are already well acquainted with Mr. Jacques Ross, who conducted a study on AIDS and insurance which we published earlier. ln this issue, Mr. Ross looks at the AIDS problem from an insurer's point of view and covers three themes: statistics, social implications and insurance. Some of the ideas presented here are already well known, but others are new and are very well researched and documented here.